Seasonal variation of size distribution of submicrometer aerosol particles at Syowa Station, Antarctica - Kazuo Osada; Chiharu Nishita-Hara; Keiichiro Hara; Masanori Yabuki; Masataka Shiobara; Makoto Wada; Takashi Yamanouchi; Masahiko Hayashi (National Institute of Polar Research, 2010)
Number-size distributions (5-168 nm in diameter) of atmospheric aerosol particles were measured at Syowa Station, Antarctica from February 2004 to January 2005. Size distributions in winter consisted of 1 to 2 modes larger than 50 nm in diameter, whereas 2 to 3 modes contributed to the size distributions in October to March with mode diameters between 20 and 80 nm. Size distribution with a valley at around 50 nm was often observed in summer to fall when the open ocean was located near Syowa Station. From September to March, concentration of ultra fine particles (<20 nm) was occasionally high. Associated with local wind pattern after vertical mixing of boundary layer air in late afternoon, high concentrations of ultra fine particles were observed for several days in late November.